2008
DOI: 10.1002/mds.22305
|View full text |Cite
|
Sign up to set email alerts
|

Chorea‐acanthocytosis: Report of two Brazilian cases

Abstract: Chorea-acanthocytosis (ChAc) is a neurodegenerative disorder characterized by chorea, neuropsychiatric disturbances and acanthocytosis, caused by mutations of VPS13A. This gene produces the protein chorein which is absent in patients with ChAc on Western blot assay. We report the first two Brazilian patients with ChAc confirmed by chorein detection. Patient 1 is a 36-year-old man with chorea, epilepsy, myopathy, and suicidal ideation. Patient 2 is a 60-year-old woman with a 30 year history of psychiatric distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Two patients met criteria for chorein testing and had absent or markedly reduced levels in peripheral blood. From these tests, we diagnosed 3 (10.3%) cases of HDL2 and 2 (6.8%) 17,18 . One patient of this study was a deceased sister of one ChAc patient, who presented with chorea and cognitive abnormalities, but whose diagnosis could not be confirmed by Western blot due to the non-availability of required biomaterial.…”
Section: Resultsmentioning
confidence: 98%
“…Two patients met criteria for chorein testing and had absent or markedly reduced levels in peripheral blood. From these tests, we diagnosed 3 (10.3%) cases of HDL2 and 2 (6.8%) 17,18 . One patient of this study was a deceased sister of one ChAc patient, who presented with chorea and cognitive abnormalities, but whose diagnosis could not be confirmed by Western blot due to the non-availability of required biomaterial.…”
Section: Resultsmentioning
confidence: 98%
“…All the participants gave informed consent and the study was approved by the local ethics committee. Rodrigues et al [2008] ? ¼ Unknown; ND ¼ not determined.…”
Section: Materials and Methods Patientsmentioning
confidence: 96%
“…Patients 1–8 include the 6 patients described in the previously described VBM study (Henkel et al 2006) and patients 1–7 reported by (Huppertz et al 2008). Patient 9 has been previously clinically described (Robertson et al 2008; Walterfang et al 2008) and patient 11 corresponds to case 2 of (Rodrigues et al 2008). Patients 12 & 13 are two previously unpublished siblings from Australia.…”
Section: Methodsmentioning
confidence: 99%